The Role of Affixation in the Formation of Meaning on Two-word bases in Sundanese - Rodhiatammardiyah, Bella; Djuharie, Otong Setiawan (Edukasi Lingua Sastra, 2025)
Indonesia is an archipelagic country rich in languages. This study discusses one of the regional languages in Indonesia, which is Sundanese. This research investigates the role of affixation in the formation of meaning on the base word two in Sundanese, contributing to the field of morphology within linguistics. The study is motivated by the limited exploration of affixation involving numerical bases in Sundanese, particularly among younger speakers who often exhibit inconsistent usage due to lack of systematic understanding. Using a qualitative content analysis method, data were collected from three Sundanese novels: Baruang Kanu Ngarora by D.K. Ardiwinata, Si Bedog Panjang by Ki Umbara, and Kabungbulengan by Hanna Djumhana Bastaman. The research identifies various forms of affixation such as prefixes (e.g., ka-, mi-, nga-), suffixes (e.g., -an, -na), and confixes (e.g., pa-…-an, mang-…-keun) that attached to the base word two. These affixes generate diverse semantic and pragmatic meanings, ranging from sequence and togetherness to actions involving two parties, as well as culturally spesific connotations like polygamy or disloyalty. The findings demonstrate that affixation in Sundanese does not merely serve morphological functions but also enriches the language’s capacity to express nuanced social and cultural interactions. This study contributes new insights to the understanding of Sundanese morphology and supports the preservation of regional languages amid rapid digital and intercultural development.